The impact of COVID-19 on clinical research: the PIPPRA and MEDRA experience [version 2; peer review: 2 approved] - Louise Larkin; Audrey C Tierney; Norelee Kennedy; Stephen Gallagher; Anusha Moses; Bente Appel Esbensen; Liam Glynn; Anne Griffin; Tala Raad; Alexander Fraser (HRB Open Research, 2023)
Background Coronavirus disease 2019 (COVID-19) has had a significant impact on clinical research. This paper aims to provide an insight into how the COVID-19 pandemic, associated public health restrictions and international guidance on the conduct of clinical research impacted two clinical rheumatology research trials - the Physiotherapist-led Intervention to Promote Physical Activity in Rheumatoid Arthritis (PIPPRA) and the MEDiterranean diet in Rheumatoid Arthritis (MEDRA) projects. Methods The March 2019 public health restrictions imposed to mitigate the risk of COVID-19 occurred at a time when PIPPRA was in the process of delivering assessment and intervention on a face-to-face basis (n=48) and MEDRA had commenced recruitment. Participants in PIPPRA and MEDRA had a diagnosis of rheumatoid arthritis, with some being immunosuppressed and thus at a higher risk for COVID-19. The decision-making processes of both trials is outlined to demonstrate the required amendments to continue in the context of the COVID-19 pandemic. Results Amendments to PIPPRA and MEDRA trial protocols were agreed and received ethical and funder approval. Both trials switched from a face-to-face delivery to a telehealth using online platforms. The PIPPRA study was paused for five months (April-August 2020), resulting in n=33 (60%) negative deviations from assessment protocol. MEDRA switched from face-to-face to online recruitment with 20% (n=35/44) negative deviations in recruitment. Of the n=18 participants who consented to participating in a face-to-face trial, just n=2 (11%) opted to engage with telehealth delivery of the intervention. MEDRA assessment and intervention deviations were 100% as no sessions were completed as planned in 2020. Conclusions The COVID-19 pandemic has severely impacted the PIPPRA and MEDRA clinical trials. Moving face-to-face clinical research to telehealth delivery may not be the panacea it is purported to be. Our experiences may be of benefit to researchers, clinicians, and funders in seeking to continue clinical research during a global pandemic.